Teacher's Use of English and Mother Tongue when Solving Discipline Problems - Podaná, Eliška (Univerzita Pardubice, 2017)
This master thesis deals with the teacher's use of the English language and mother tongue when solving discipline problems. It is divided into the theoretical and practical part. The main aim of the theoretical part is to introduce the essential concepts such as mother tongue, second language, discipline, uncooperative behaviour of learners, types of misbehaviour and strategies for dealing with misbehaviour. The practical part concentrates on a multiple-case study which was carried out at one selected basic school and three teachers of the English language were involved in the study.
Využívání anglického a mateřského jazyka učitelem při řešení problémů s disciplínou
Keywords: komunikativní kompetence; mateřský jazyk; druhý jazyk; disciplína; nevhodné chování; spolupracující a nespolupracující chování; intervenční strategie; communicative competence; mother tongue; second language; discipline; misbehaviour; cooperative and uncooperative behaviour; intervention strategies